Evaluation of dentinal defects during root canal preparation using thermomechanically processed nickel-titanium files - Kesim, Bertan; Sagsen, Burak; Aslan, Tugrul (European Journal of Dentistry, 2017)
Objective: The aim of this study was to compare the incidence of root cracks after root canal instrumentation with thermomechanically processed nickel-titanium (Ni-Ti) files with different instrumentation kinematics. Materials and Methods: A total of 150 extracted mandibular premolars with mature apices and straight root canals were divided into five groups and used in this study. In Group 1, 30 teeth were prepared using hand K-files and assigned to control group, Group 2 was instrumented using K3XF Rotary files (SybronEndo, Glendora, CA, USA) with continuous rotary motion. The teeth in Group 3 were instrumented by ProTaper Next (Dentsply Maillefer, Ballaigues, Switzerland) rotary files which make asymmetric rotary motion, In Group 4, teeth were instrumented by RECIPROC (VDW, Munich, Germany) with reciprocation motion and in Group 5, teeth were instrumented by Twisted File (TF) Adaptive (SybronEndo, Orange, CA, USA) files that use combination of continuous rotation and reciprocation motion (n = 30/per group). All the roots were horizontally sectioned 3, 6, and 9 mm from the apex with a low speed saw under water cooling. Then, the slices were examined through a stereomicroscope to determine the presence of dentinal microcracks.Results: For the apical (3-mm) and coronal (9-mm) sections, the ProTaper Next and TF Adaptive produced significantly more cracks than the hand files, RECIPROC, and K3XF (P < 0.05). There was no significant difference between the experimental groups and control group at the 6-mm level (P > 0.05). Conclusions: Within the limitations of this in vitro study, all thermal-treated Ni-Ti instruments and hand files caused microcracks in root canal dentin.
Keywords: Kinematic; M-wire; microcracks; nickel-titanium instruments; R-phase; thermal treatment